Analisis Romantisme dan Makna Hiperbola Pada Puisi “Syair Rindu” Karya Marah Roesli - Irfanda Siti Amaliyafitri (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2022)
This article discusses the hidden meaning of the poem by Marah Roesli. This discussion aims to better understand the reader about the content of the poem. The poem